Safety First: Technology, Labor, and Business in the Building of American Work Safety, 1870-1939 - Tucker, Eric (Labour / Le Travail, 1998)
The article reviews the book, "Safety First: Technology, Labor, and Business in the Building of American Work Safety, 1870-1939," by Mark Aldrich.